Effect of Er:YAG Laser for Women with Stress Urinary Incontinence. (15th January 2019) - Lin, Kun-Ling; Chou, Shih-Hsiang; Long, Cheng-Yu
Abstract : Purpose . The aim of our study is to assess efficacy of noninvasive erbium-doped yttrium aluminium garnet laser (Er:YAG laser) for female stress urinary incontinence (SUI). Materials and Methods . Forty-one women with SUI were included in the study and scheduled for vaginal Er:YAG laser treatment. The procedure was performed with a 2940 nm, Er:YAG laser (Fotona Smooth ™ XS, Fotona, Ljubljana, Slovenia), designed to heat up the vaginal mucosa to around 60°C. All subjects had a baseline and 6 months' posttreatment assessment that included perineal sonography and lower urinary tract symptoms. Results . Significant improvements in both urinary frequency and incontinence were found 6 months after Er:YAG laser treatment when compared to the baseline results (p<0.001). The battery of questionnaires administered to patients, including the UDI-6, IIQ-7, OABSS, and POPDI-6, all showed significant improvement posttreatment (P < 0.001). The treatment efficacy for the vaginal Er:YAG laser for SUI at 6 months posttreatment was 75.5% (31/41). Bladder neck mobility by perineal ultrasonography decreased significantly (16.1 ± 6.4 mm to 10.5 ± 4.6 mm) after treatment (p=0.039). No permanent adverse events were found. Conclusions . The Er:YAG vaginal laser seems to be a safe and efficacious treatment for women with mild to moderate SUI, this being partly related to the decrease of bladder neck mobility following laser treatment.